The Role of Citizenship Education in Raising Awareness of Citizens' Rights and Obligations among UNIMED Students - Sembiring, Aynen Kresensia Br; Pardosi, Mernawati; La’ia, Miranda; Wantoya, Qiara; Purba, Rani Eviolina; Pratiwi, Yulia Citra; Yunita, Sri (Formosa Journal of Science and Technology, 2024)
A student must have an awareness of his rights and obligations as a citizen, to carry them out with full responsibility. Therefore, the purpose of this research is to find out how much the role of citizenship education in increasing awareness of the rights and obligations of citizens according to the views of UNIMED students.  The research method used from this research is Qualitative research method, which collects information from journals as well as data and findings from questionnaires distributed to UNIMED students. From the research that has been conducted, it is found that UNIMED students think that citizenship education plays an active role in increasing awareness of rights and obligations as citizens at the student level.